Four Basic Skills Proficiency Based on Students' Perception in Hospitality & Tourism Study Program, Bunda Mulia University - Supina Supina (Universitas Bunda Mulia, 2018)
Wide open employment in the tourism industry leads to the urgent needs for ready to work manpower. In the tourism industry, the readiness of the workforce in addition to the operational skills of the work is the ability of foreign language that is widely used globally in the world, in this case is English. Tourism education institutions as tourism human resources factories not only must prepare operational skills, but also English skills which is important to avoid complaints from graduates’ saying that educational institutions do not provide sufficient English supplies. In order to provide sufficient English supplies, student’s English proficiency should be known at this time along with the reason, to know what can improve student’s spirit of learning, because English for Tourism Purposes (ETP) can not be measured only by tests such as TOEFL / TOEFL / IELTS. The results of this study is expected to be a improvement material to improve the quality of every tourism student’s English in order to prepare graduates who are ready to work in a Global environment.Keywords: English for Tourism Purposes, Proficiency, Four Basic Skills